Hubungan antara Pola Asuh Orang Tua dan Perkembangan Motorik Halus pada Anak Usia 3-4 Tahun di PAUD Permata Hati SPNF SKB Kota Malang - Natania, Marsha Arga; Yusuf, Ali (J+PLUS UNESA, 2023)
Growth and development itself is an interaction between children with genetic factors and environmental factors (family). The quality of interactions or relationships in the environment around the child, especially those carried out by a child with parents, is very important because parenting plays an important role in monitoring and facilitating children to grow and develop properly, especially in fine motor development. The purpose of this study was to determine the relationship between parenting patterns and fine motor development at PAUD Permata Hati SPNF SKB Malang City with a sample size of 24 parents of children aged 3-4 years. This study used a correlational quantitative approach. Data were collected using a questionnaire and observation which were analyzed using the Spearman Rank or Spearman Rho test. The results showed that there was an average of parents applying democratic parenting with most children at the level of fine motor development developing very well as many as 14 children (58.3%) with the results of the analysis obtained a value of 0.522 which states that there is a strong and unidirectional relationship between parenting and fine motor development in children aged 3-4 years at PAUD Permata Hati SPNF SKB Malang City.